2019
DOI: 10.1002/14651858.cd005253.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Iodine supplementation for the prevention of mortality and adverse neurodevelopmental outcomes in preterm infants

Abstract: Iodine supplementation for the prevention of mortality and adverse neurodevelopmental outcomes in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…In a recent study in three major cities across the UK, researchers found no relation between iodine deficiency and low birth weight and preterm labour [40]. Walsh et al did not find any relation between maternal low iodine intake and perinatal mortality and neural development of the neonates of these mothers [41].…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study in three major cities across the UK, researchers found no relation between iodine deficiency and low birth weight and preterm labour [40]. Walsh et al did not find any relation between maternal low iodine intake and perinatal mortality and neural development of the neonates of these mothers [41].…”
Section: Discussionmentioning
confidence: 96%
“…Five SRs (3,14,18,24,25) reported no impact of the interventions on the preterm infants. These supplements were inositol, iodine, fat, glutamine, and LCPUFA.…”
Section: No Impactmentioning
confidence: 99%
“…Walsh et al (14) and Amissah et al (18) concluded there was no impact of the iodine and fat supplementation owing to the outcome of no health improvement. Another 3 SRs (3, 24, 25) did not nd any evidence supporting their major outcome improvements though some positive results were observed.…”
Section: No Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular relevance are the detrimental effects of an insufficient maternal intake of iodine on development and maturation of the fetal brain, which represents a foremost preventable cause of mental defects [10]. Further adverse effects include abortion, stillbirth, impairment of cognitive functions, delayed growth and puberty, hypothyroidism, goiter, and infertility [11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%